Students' Perception Of Using Google Form In English Test At English Education Departement Of STAI Hubbulwathan Duri - Dwi Sukmawati, Indah (Jolly Journal of English Education, 2024)
The purpose of this study was to find the perception of TBI students using Google Form in the English test. The design of the research was a survey. In this research, the writer conducted a descriptive survey. The sample in this study was 32 students. The data collection techniques used tests; questionnaires and documentation. According to the poll results, 23.5% of the majority of students said that using Google Forms helped them learn to read and made the process easier. Regarding the use of Google Forms, 11.25% of students are neutral, 15.5% of students disagree, 8.25% of students definitely disagree, and 42% of students strongly agree. These findings reveal many drawbacks to using Google Forms as well as the perception of students that using them positively improves learning despite the possibility of cheating.